The Bitter Taste Receptor TAS2R16 Achieves High Specificity and Accommodates Diverse Glycoside Ligands by using a Two-faced Binding Pocket - Anu Thomas (Nature Portfolio, 2017)
Abstract Although bitter taste receptors (TAS2Rs) are important for human health, little is known of the determinants of ligand specificity. TAS2Rs such as TAS2R16 help define gustatory perception and dietary preferences that ultimately influence human health and disease. Each TAS2R must accommodate a broad diversity of chemical structures while simultaneously achieving high specificity so that diverse bitter toxins can be detected without all foods tasting bitter. However, how these G protein-coupled receptors achieve this balance is poorly understood. Here we used a comprehensive mutation library of human TAS2R16 to map its interactions with existing and novel agonists. We identified 13 TAS2R16 residues that contribute to ligand specificity and 38 residues whose mutation eliminated signal transduction by all ligands, providing a comprehensive assessment of how this GPCR binds and signals. Our data suggest a model in which hydrophobic residues on TM3 and TM7 form a broad ligand-binding pocket that can accommodate the diverse structural features of β-glycoside ligands while still achieving high specificity.